Pharmacokinetic studies and anticancer activity of curcumin-loaded nanostructured lipid carriers - Wang Fengling; Chen Jin; Dai Wenting; He Zhengmin; Zhai Dandan; Chen Weidong (Acta Pharmaceutica)
In order to investigate the potential of nanostructured lipid carriers for efficient and targeted delivery of curcumin, the pharmacokinetic parameters of curcumin-loaded nanostructured lipid carriers (Cur-NLC) were evaluated in rats after a single intraperitoneal dose of Cur-NLC. In addition, the anticancer activity of Cur-NLC against human lung adenocarcinoma A549 cells was verified by a cellular uptake study, and a cytotoxicity and apoptosis assay. Bioavailability of Cur-NLC was better than that of native curcumin (p > 0.01), as seen from the area under the plasma concentration-time curve (AUC), maximum plasma concentration (Cmax), mean residence time (MRT) and total plasma clearance (CLz/F). Cur-NLC has a more obvious lung-targeting property in comparison with native curcumin. Cur-NLC showed higher anticancer activity in vitro against A549 cells than native curcumin (IC50 value of 5.66 vs. 9.81 mg L−1, respectively). Meanwhile, Cur-NLC treated A549 cells showed a higher apoptosis rate compared to that of native curcumin. These results indicate that NLC is a promising system for the delivery of curcumin in the treatment of lung adenocarcinoma.